Ethical Aspects in the Organization of Legislative Information - Brandt, Mariana Baptista (Knowledge organization, 2018)
The goal of this research is to analyze ethical questions related to the organization of legislative information (bills, laws, and speeches) within the scope of the Brazilian Federal legislature (Chamber of Deputies and Federal Senate). Field research including interviews was used to collect data in order to investigate the development of knowledge representation tools, such as thesauri and taxonomies, and subject indexing for organization of legislative information (bills, legislation, and speeches). The heads of all sectors responsible for the chosen activities were interviewed in person, and the answers were compared to common ethical problems described in knowledge organization (KO) literature. The results, in part, show a lack of clarity on ethical issues in the treatment of legislative information, pointing to ethical dilemmas and identifying problems such as informational directness, misrepresentation, and ambiguity, among others. The indexers in the Brazilian Congress found ambiguity the ethical aspect faced most often in their jobs. The next most frequent issue was professional inefficiency and in third place was a tie between informational directness and lack of cultural warrant. The research also describes solutions used for various ethical dilemmas. It was found that some indexing terms used to describe bills in the Brazilian Chamber of Deputies have been subject to censorship and censored, or censurable, indexing terms have to be hidden in metadata so documents can be retrieved by users. It concludes that a greater ethical awareness of technical aspects is needed for Brazilian Federal legislative information professionals.